Dual Microcatheter Technique for Coiling of Intracranial Aneurysms: 2-Dimensional Operative Video. Issue 6 (24th March 2021) - Waqas, Muhammad; Dossani, Rimal H; Cappuzzo, Justin M; Sonig, Ashish; Becker, Alexander B; Levy, Elad I
Abstract: Primary coiling of large intracranial aneurysms with complex morphology, such as multiple lobes and a wide neck, is challenging. In these aneurysms, achieving adequate intra-aneurysmal packing density while preventing coil herniation into the parent vessel may be difficult with traditional coiling technique. In the setting of acute aneurysm rupture, alternative treatment options such as stent-assisted coiling or flow diversion may not be feasible due to the need for dual antiplatelets. In this video, we demonstrate the use of a dual microcatheter technique to achieve adequate packing density within a wide-necked, bilobed saccular aneurysm. The patient presented with a ruptured posterior communicating artery aneurysm with Hunt and Hess grade 2 and Fisher grade 4 subarachnoid hemorrhage. A biaxial catheter system was used for primary coiling of the aneurysm. Two .017-inch microcatheters were strategically positioned in the aneurysm lobes. The first coil was deployed through the distal catheter, which created a basket for the second coil to be deployed through the proximal microcatheter. Subsequent simultaneously deployed coils were weaved into each other to form a stable coil mass that prevented coil herniation into the parent vessel. Complete obliteration of the aneurysm was achieved. The patient gave informed consent for the procedures and video recording. Institutional review board approval was deemed unnecessary. Video. ©University at Buffalo Neurosurgery, Inc., January 2020. With permission.